Essential Oil Extraction, Chemical Analysis and Anti-Candida Activity of Calamintha nepeta (L.) Savi subsp. glandulosa (Req.) Ball—New Approaches - Božović, Mijat (Molecules, 2017)
A comprehensive study on essential oils extracted from different Calamintha nepeta (L.) Savi subsp. glandulosa (Req.) Ball samples from Tarquinia (Italy) is reported. In this study, the 24-h steam distillation procedure for essential oil preparation, in terms of different harvesting and extraction times, was applied. The Gas chromatography–mass spectrometry (GC/MS) analysis showed that C. nepeta (L.) Savi subsp. glandulosa (Req.) Ball essential oils from Tarquinia belong to the pulegone-rich chemotype. The analysis of 44 samples revealed that along with pulegone, some other chemicals may participate in exerting the related antifungal activity. The results indicated that for higher activity, the essential oils should be produced with at least a 6-h steam distillation process. Even though it is not so dependent on the period of harvesting, it could be recommended not to harvest the plant in the fruiting stage, since no significant antifungal effect was shown. The maximum essential oil yield was obtained in August, with the highest pulegone percentage. To obtain the oil with a higher content of menthone, September and October should be considered as the optimal periods. Regarding the extraction duration, vegetative stage material gives the oil in the first 3 h, while material from the reproductive phase should be extracted at least at 6 or even 12 h.